FEATURES HIP ARTHROPLASTY AFTER REDUCTIONRECONSTRUCTIVE INTERVENTIONS OF PROXIMAL FEMUR - B. Sh. Minasov; R. R. Yakupov; T. E. Hairov; I. R. Gafarov; K. K. Sirodzhov; K. K. Karimov; G. .N. Filimonov; A. R. Trubin (Исследования и практика в медицине)
Abstract:Surgical treatment of destructive and degenerative diseases of the hip arthroplasty technology with the modern development of science, technology and medicine is considered the most effective method of providing social and personal reintegration. However, the opinion of experts, arthroplasty increases the complication rate in patients after osteosynthesis and osteotomy of the proximal femur. The purpose of research - to compare patient outcomes Technology hip arthroplasty after-reducing reconstructive interventions at the proximal femur. Material and Methods: The study group comprised 42 patients who underwent hip arthroplasty after-reducing reconstructive interventions at the proximal femur. The control group consisted of 43 patients with idiopathic hip osteoarthritis who underwent primary arthroplasty. Results: conducting joint replacement in patients of the main group was accompanied by an increase in the frequency of intraoperative and postoperative complications. Therefore, this group of patients requires a special approach to diagnosis and treatment.